Hypothyroidism and Its Association with Delayed Pregnancy and Hormonal Imbalances in Women of the Jabal al AKhder Region - Saliha Gadalla Alsanosy Abdulsayid; Saada Saleh Abdulgader Ali (African Journal of Advanced Pure and Applied Sciences, 2025)
This cross-sectional study investigated the impact of hypothyroidism on female fertility, defined as the capacity to establish a clinical pregnancy. Given the significant prevalence of hypothyroidism (estimated at 2-4%) among women of reproductive age, this research was conducted in the Green Mountain region of Libya between August 2024 and February 2025. A cohort of 100 women aged 18-45 years was recruited from hospitals and private clinics in Al-Bayda, Shahat, Derna, Al-Qubbah, and Ain Mara. Serum concentrations of prolactin, thyroid-stimulating hormone (TSH), luteinizing hormone (LH), follicle-stimulating hormone (FSH), triiodothyronine (T3), and thyroxine (T4) were quantified. The study population comprised 60 hypothyroid patients exhibiting subfertility and 40 healthy controls. Analysis revealed significantly elevated (p<0.05) TSH and prolactin levels in hypothyroid patients compared to controls. Conversely, total T4, T3, LH, and FSH levels were significantly reduced (p<0.05) in the patient group. Alterations in the FSH/LH ratio were observed, potentially associated with diminished estrogen levels and ovulatory dysfunction in hypothyroidism. Sustained minimal estrogen concentrations may underlie the prevalent menorrhagia reported in this cohort. Additionally, hypothyroid patients demonstrated a higher propensity for overweight compared to controls. These findings underscore the significant association between hypothyroidism, reproductive hormone dysregulation, and impaired fertility in women.